2017
DOI: 10.1146/annurev-clinpsy-032816-045217
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Treatments for the World: Lessons from Low- and Middle-Income Countries

Abstract: Common mental disorders, including depression, anxiety, and posttraumatic stress, are leading causes of disability worldwide. Treatment for these disorders is limited in low- and middle-income countries. This systematic review synthesizes the implementation processes and examines the effectiveness of psychological treatments for common mental disorders in adults delivered by nonspecialist providers in low- and middle-income countries. In total, 27 trials met the eligibility criteria; most treatments targeted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
509
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 628 publications
(559 citation statements)
references
References 107 publications
(127 reference statements)
20
509
0
1
Order By: Relevance
“…A recent systematic review has demonstrated the effectiveness of psychological therapies delivered by non-specialists in low-resource settings 52 . Such therapies may be modified when delivered in the context of high inequality through a focus on mechanisms related to cognitive comparisons leading to social defeat and worthlessness.…”
Section: Implications For Reducing the Global Burden Of Depressionmentioning
confidence: 99%
“…A recent systematic review has demonstrated the effectiveness of psychological therapies delivered by non-specialists in low-resource settings 52 . Such therapies may be modified when delivered in the context of high inequality through a focus on mechanisms related to cognitive comparisons leading to social defeat and worthlessness.…”
Section: Implications For Reducing the Global Burden Of Depressionmentioning
confidence: 99%
“…Studies evaluating task-shifting interventions in mental health care have been carried out in LMICs, and show positive results in terms of reducing disability and improving overall and social functioning (Singla et al, 2017; van Ginneken et al, 2013). An RCT in India (Patel et al, 2010) showed that a collaborative care intervention led by lay counsellors was cost-saving to the health system (Buttorff et al, 2012).…”
Section: Scaling-up Mental Health Interventions For Refugeesmentioning
confidence: 99%
“…These treatments, largely based on cognitive—behavioural and interpersonal theoretical frameworks, are typically delivered by nonprofessional frontline workers (such as community health workers) in primary care or community-based settings in six to ten sessions over two to three months. A large body of evidence—including 27 trials in a recent review [13] and bolstered by several more recent trials [8,14]—testifies to the high levels of acceptability, large effects, and good value for money that these interventions offer. The scaling up of these treatments through routine primary care or other health care platforms (notably maternal health care, for which an equally impressive body of evidence demonstrates the effectiveness of nonspecialist-delivered psychological treatments [15]) should now focus on integrating the management of depressive disorder with other common mental disorders (anxiety disorders and somatoform disorders) through transdiagnostic interventions [16] and, more broadly, with other chronic conditions.…”
Section: A Staged Model Of Depressionmentioning
confidence: 99%